Pancytopenia with Development of Persistent Neutropenia Secondary to COVID-19 - Kathie Wu; Yvonne Dansoa; Priyanka Pathak (Case Reports in Hematology)
Viral infections have long been linked to hematologic dysfunction. With the rapid spread of COVID-19, various hematologic manifestations have emerged. While there have been several reports of immune thrombocytopenic purpura from SARS-CoV-2, concurrent lymphopenia and anemia have sparse. We describe a case of COVID-induced pancytopenia that presented months after initial COVID infection that initially responded to IVIG and steroids, but now with persistent neutropenia.